From Evil Queen to Disabled Teen: Frozen Introduces Disney's First Disabled Princess - Michelle Resene (Disability Studies Quarterly, 2017)
Disney's Frozen represents a landmark for the animation giant due not only to its immense popularity but also its introduction of the studio's first disabled princess. In order to make Elsa's story possible, the animators use a combination of narrative devices including the introduction of a second princess, whose story fulfills the audience's expectation for a traditional "princess journey," their patented aesthetic of cuteness, and the encoding of disability as fantasy. Although Elsa's disability is encoded as a magical ice power, the language the film uses to talk about her condition maps on to the experiences of people with physical, mental, and intellectual disabilities in recognizable ways. Meanwhile, her status as a much-beloved princess figure allows the animators at Disney to position disability as a universal experience and in turn to create empathy for PWDs both on and off screen.